(untitled) (Journal of Philosophy Culture and Political Science, 2021)
A new concept of an online research and training platform for the implementation of collaborative thematic projects, particularly in the SHS field, LABΩ enables the rapid launch and successful completion of a research programme virtually mobilising an international, multidisciplinary and multi-level network (from the enlightened amateur to the PR via the doctoral student) without having to seek funding but solely on the basis of the scientific interest of the project. The article was first published in French in the form of an interview with the director of the Gilles Gaston Granger Center P. Taranto (Dématérialiser la recherche pour revenir à l’essentiel: le projet LABΩ // La Lettre de l’InSHS, №66, juillet 2020, pp. 14-17). The article reveals the details of one of the center’s scientific projects on the implementation of scientific research in the field of humanities in the modern digital world. The authors answer the question of how digitalization processes affect the process and methodology of scientific work in the digital world, as well as reveal the essence of the digital tools offered by the platform LABΩ for this. The article is published as part of the implementation of a joint EuropeanKazakhstan project “Digital humanities in the Republic of Kazakhstan: local solutions for global problems” co-funded by the Erasmus+ Programme of the European Union. The project includes lectures, the creation of MOOC courses, and a number of scientific publications. The authors of the article invite Kazakhstani researchers to discuss and share experiences on the topic of digital humanitarian research in the Republic of Kazakhstan. Key words: digital humanities, digitalization, international projects, LABΩ, Republic of Kazakhstan.